THE ANALYSIS OF METHODS OF AN ECONOMIC JUSTIFICATION OF DEVELOPMENT OF CORPORATE INFORMATION SYSTEMS IN THE INDUSTRY - N. Arseneva; D. Pelihov; M. Sazonova (Вестник университета)
In the article results of the analysis of domestic and foreign literature on problems of an economic justification of corporate information systems in the industry are stated. Definition of corporate information system is given. The reasons of failures at automation of productions at the enterprises of mechanical engineering are established.